Rational catalyst design for carbon nanotube carpet growth and Fischer-Tropsch synthesis - Li, Xu (Kansas State University, 2019)
The first part of this research involves the growth of vertically aligned carbon nanotube (CNT) arrays (or CNT carpets) that are desired in many important applications. Growth of high-quality, dense CNT carpets via catalytic chemical vapor deposition (CCVD) has been largely limited to catalysts supported on amorphous alumina or silica. Although catalyst design and CCVD process optimization have been extensively investigated, scalable growth of CNT carpets especially on nontraditional substrates remains largely a challenge. To develop a rational basis for designing efficient CNT catalysts, a deeper understanding of the role of substrates in CNT carpet growth during CCVD is required. In this study, a fundamental investigation of the effects of substrate properties on CNT carpet growth from supported catalysts under different reaction conditions and feedstock is carried out. To illuminate the interrelationships between properties of catalyst supporting layers on CNT carpet growth behaviors, CNT growth experiments from Fe catalyst supported on a variety of nontraditional substrates including stainless steel (SS), MgO, MgAl₂O₄ (100, 110, and 111 crystalline phases), and ZrO₂ were carried out. This study reveals that ion beam bombardment of 316 SS decreases the film thickness of AlxOy required for CNT growth to 5 nm AlxOy. The role of ion beam bombardment is to transform a highly crystalline surface into an amorphous surface, resulting in favorable catalyst-substrate interactions that enhances CNT growth. Our results reveal that Fe catalyst supported on different phases of MgAl₂O₄ spinel substrates show different CNT growth behaviors due to their different surface chemistries and surface energies. The second part of this research is motivated by the drive to seek new routes that yield clean fuels and chemicals via Fischer-Tropsch synthesis (FTS). FTS provides a pathway for the transformation of biomass, coal or natural gas into fuels and chemicals using a transition metal catalyst. Co-based catalysts are of interest because they exhibit relatively higher activity and selectivity to long-chain paraffins, high resistance to deactivation, and a low water-gas shift (WGS) reaction activity. Catalytic performance is sensitive to the catalyst preparation method and type of catalyst precursor. To investigate the effect of the type of catalyst precursor used during synthesis on physicochemical properties and efficiency of FTS process, SiO₂-supported Co catalysts were synthesized via an incipient wetness impregnation method from four different precursors: Co(NO₃)₂ (Co-Nit), Co(C₂H₃O₂)2 (Co-Ace), CoCl₂ (Co-Chl), and Co(OH)₂ (Co-Hyd). This study reveals the type of Co precursor used during synthesis has significant effects on catalyst dispersion, size, crystalline phase, reducibility, stability, and FTS performance (CO conversion, C5+ selectivity, turnover frequency, and catalyst lifetime). Prenatal and postmortem characterization of the catalyst reveal sintering and formation of Co₂C in all catalysts except Co-Nit, which may explain the various degrees of deactivation observed. Further, XANES and EXAFS data confirm the superior structural stability of Co-Hyd and presence of hydroxyl groups even after reaction.
Keywords: Carbon Nanotubes; Substrate; Ion beam bombardment; Crystal phase; Fischer-Tropsch; Cobalt precursors